التمثيل الخرائطي لبعض خصائص سكان منطقة الجفارة (دراسة تطبيقية باستخدام تقنية نظم المعلومات الجغرافية) (Libya Journal of Geographical Studies, 2023)
study aims to prepare , produce population digital maps for som characteristics of population in Al-Jaffara region, and highlight spatial ,temporal numerical, relative and environmental variation, and places of concentration and dispersion according to branches and shops due to importance of this in social and economic planning, according to statistics of census of (2006), and estimates for the year (2020). study tracked the absolute and relative spatial changes that occurred in population size, and its cartographic representation based on ARC GIS 10.8 Geographic Information Systems program, based on three methods of cartographic representation, so researcher used to calculate the numerical and environmental distribution of population of shops using point distribution method, because it higher visual perception was achieved than color gradient distribution or graphic representation, and gradient method in symbol sizes was used to represent general density, taking into account changing the symbol size to match scale of map. also showed possibility of representing statistical data in one map in more than one way, by following method of merging Between the two methods of color gradient distribution (corropleth) to represent absolute numbers ,and suitable method of symbol size for the value or statistical percentage it represents to represent relative values, to higher visualperception achieve that gives clear picture to non-specialist reader of spatialvariation of distribution. study concluded more than two-thirds of population of the Jafara region are concentrated in less than two-thirds of its area, which indicates their distribution is uneven, and their concentration almost same for all branches during study period, and general density varies from one census to another and from one place to another. This according to geographical location of each branch, level of services it enjoys, and its proximity to Tripoli, where the general density increases in Janzour branch, then in northern part of Zahraa branch, then Al- Sawani branch, and northeastern part of Arba'a branch, while decreases in southern and southeastern ends of branch, and also decreases in the Aziziyah branch, especially southern and southwestern ends.
Keywords: cartographic representation; geographic information systems; general population densit